Controls for Cross-Border Payments Operations: Correspondent Banking Risk Reduction via End-to-End Monitoring - Blessing Olajumoke Farounbi; Olaolu Samuel Adesanya; Akindamola Samuel Akinola; Chizoba Michael Okafor (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cross-border payments have become an essential component of global financial networks, enabling businesses, financial institutions, and individuals to transfer funds across jurisdictions. However, correspondent banking relationships, which facilitate these transfers, carry inherent operational, compliance, and financial risks, including fraud, money laundering, sanctions violations, and settlement delays. This paper investigates the implementation of end-to-end monitoring mechanisms as a control framework for reducing risk in correspondent banking operations. Leveraging a combination of process mapping, risk assessment matrices, automated transaction monitoring tools, and exception management protocols, the study identifies the most effective approaches for enhancing transparency, operational efficiency, and regulatory compliance. The research employs a mixed-methods approach, including case study analyses of major financial institutions, quantitative modeling of payment flows, and simulation experiments to evaluate the performance of different monitoring architectures. Results demonstrate that comprehensive end-to-end monitoring can reduce operational risk by up to 35%, improve anomaly detection by 42%, and significantly mitigate financial exposure to correspondent bank failures. The findings contribute to the theoretical understanding of risk management in cross-border payment systems and provide actionable recommendations for financial institutions seeking to optimize their controls while maintaining operational efficiency. Furthermore, the study highlights the importance of integrating real-time monitoring, standardized data protocols, and multi-layered exception handling in a manner that balances regulatory requirements with business objectives. Overall, the paper presents a structured framework for risk reduction in correspondent banking operations that can be adapted across diverse financial networks.
Keywords: Cross-Border Payments; Correspondent Banking; Risk Monitoring; Operational Controls; Transaction Compliance; End-to-End Oversight